Contribution of Madhabadevato the Intellectual Arena of Assam, India - Goswami, Nandita (International Journal of Psychosocial Rehabilitation, 2020)
Madhabadeva (1489-1596) is one of the most popular preceptors of Ekasarana Dharma. After Sankaradeva, he is the next outstanding figure in Assamese literature. Assam is known as the state of Ekasarana Dharma because of these two legends, Sankaradeva and Madhabadeva. Madhabadeva made a significant contribution to the development of his Guru Sankaradeva's legacy to enlighten the people of that era. There is also a graceful flow in Madhabadeva’s style which is as expressive and captivating as that of his master. Madhabadeva’s contributions to the modern dramas are also significant works for the Assamese literature of that period. He is known particularly for his book of hymns, the ‘Naam Ghosha’. This gave a strong impetus towards Assamese literature. The Borgeet written by both Sankardeva and Madhabadeva is known as the soul song of Assam. Following Sankaradeva, the great Neo-Vaishnaviate reformer Madhabadeva spent his most valuable time in pursuing the doctrines of Vaishnava literature Madhabadeva, and his cultivation of Vaishnava literature through his significant works are like a rebirth and transformation from darkness into light for the last six centuries. This is a philosophical study of Madhabadeva’s literary output which has a great place in literature of Assam. The vision of this study is to explore Madhabadeva’s philosophical contribution towards the literary culture of Assamese society.